The Evolution of Educational Game Designs From Computers to Mobile Devices: A Comprehensive Review - Tlili, Ahmed; Essalmi, Fathi; Jemni, Mohamed; Kinshuk; Chen, Nian-Shing; Huang, Ronghuai; Burgos, Daniel (Lecture Notes in Educational Technology, 2020)
With the rapid growth of mobile technologies, mobile devices have become very popular and have reached a very high spread. Consequently, mobile games have started gaining an increasing attention from researchers and practitioners. This paper investigates the impact of mobile technologies on designing and delivering educational mobile games. In particular, it investigates the evolution of educational games design from being used on computers to being used on mobile devices. To do so, forty studies regarding computer and mobile educational games are reviewed. The obtained results showed that: (1) computer and mobile educational games still share some game design elements. (2) the new embedded mobile devices’ technologies made educational mobile games more immersive and fun. (3) a set of game design recommendations regarding designing mobile educational games which researchers and practitioners can refer to in their context.
Keywords: game design; mobile technologies; computer educational games; mobile educational games; Scopus(2)